Colorectal Adenomas-Genetics and Searching for New Molecular Screening Biomarkers - Siskova, Anna; Cervena, Klara; Kral, Jan; Hucl, Tomas; Vodicka, Pavel; Vymetalkova, Veronika (International journal of molecular sciences, 2020)
Colorectal cancer (CRC) is a malignant disease with an incidence of over 1.8 million new cases per year worldwide. CRC outcome is closely related to the respective stage of CRC and is more favorable at less advanced stages. Detection of early colorectal adenomas is the key to survival. In spite of implemented screening programs showing efficiency in the detection of early precancerous lesions and CRC in asymptomatic patients, a significant number of patients are still diagnosed in advanced stages. Research on CRC accomplished during the last decade has improved our understanding of the etiology and development of colorectal adenomas and revealed weaknesses in the general approach to their detection and elimination. Recent studies seek to find a reliable non-invasive biomarker detectable even in the blood. New candidate biomarkers could be selected on the basis of so-called liquid biopsy, such as long non-coding RNA, microRNA, circulating cell-free DNA, circulating tumor cells, and inflammatory factors released from the adenoma into circulation. In this work, we focused on both genetic and epigenetic changes associated with the development of colorectal adenomas into colorectal carcinoma and we also discuss new possible biomarkers that are detectable even in adenomas prior to cancer development.
Keywords: regulace genové exprese u nádorů; nádorové biomarkery; Biomarkers, Tumor; Cell Transformation, Neoplastic; Humans; nádorová transformace buněk; zvířata; genetická variace; Early Detection of Cancer; časná detekce nádoru; Gene Expression Regulation, Neoplastic; Disease Susceptibility; Genetic Variation; kolorektální nádory; náchylnost k nemoci; Animals; lidé; adenom; Adenoma; Colorectal Neoplasms